2000
DOI: 10.1038/labinvest.3780152
|View full text |Cite
|
Sign up to set email alerts
|

FISH Analysis of Gene Aberrations (MYC, CCND1, ERBB2, RB, and AR) in Advanced Prostatic Carcinomas Before and After Androgen Deprivation Therapy

Abstract: SUMMARY:Genetic mechanisms leading to androgen-independent growth in advanced prostatic carcinomas (PC) are still poorly understood. Analysis of genes potentially involved in the regulation of tumor cell proliferation and apoptosis might confer better insight into this process and might lead to improved therapeutic strategies. Fluorescence in situ hybridization (FISH) analysis of dissociated nuclei with DNA probes for MYC (8q24)/#8, cyclin D1 gene (CCND1; 11q13)/#11, ERBB2 (17q13)/#17, the androgen receptor ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 22 publications
5
53
0
3
Order By: Relevance
“…We previously reported AR amplification and overexpression in 30% of the CaPs that recurred during ADT (Bubendorf et al, 1999;Koivisto et al, 1997;Visakorpi et al, 1995). In the present study, the prevalence of AR gene amplification was 25%, which is in line with reports from other laboratories (Kaltz-Wittmer et al, 2000;Miyoshi et al, 2000). The tumors with amplification were equally distributed among the therapy groups, suggesting that orchiectomy, estrogen therapy, and a combination therapy of orchiectomy and EMP are able to cause such a reduction in intraprostatic DHT levels that the growth of malignant cells is disturbed and only cell clones with selective growth advantages, such as extra AR copies, are survived under the androgendeficient milieu.…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported AR amplification and overexpression in 30% of the CaPs that recurred during ADT (Bubendorf et al, 1999;Koivisto et al, 1997;Visakorpi et al, 1995). In the present study, the prevalence of AR gene amplification was 25%, which is in line with reports from other laboratories (Kaltz-Wittmer et al, 2000;Miyoshi et al, 2000). The tumors with amplification were equally distributed among the therapy groups, suggesting that orchiectomy, estrogen therapy, and a combination therapy of orchiectomy and EMP are able to cause such a reduction in intraprostatic DHT levels that the growth of malignant cells is disturbed and only cell clones with selective growth advantages, such as extra AR copies, are survived under the androgendeficient milieu.…”
Section: Discussionsupporting
confidence: 83%
“…Prostate cancer is the most common noncutaneous malignancy diagnosed in American men (25), but there is only a limited understanding of its genetic and molecular basis (26). Different studies have shown that c-Myc mRNA is commonly overexpressed in hyperplasic and malignant prostate (27), and the c-Myc gene is amplified in between 11% and 40% of prostate cancers in different studies (28)(29)(30). Although c-Myc amplification has been mainly associated with metastatic progression, c-Myc is also amplified at lower levels in initial stages of prostate carcinogenesis (30).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 null mice exhibit deficiencies in mammary gland development, including specific defects in alveolar growth [75,76], a phenotype similar to adult female mice lacking PR-B [77]. Cyclin D1 mRNA and protein levels increase in response to estrogen, progesterone, or androgen treatment [17,78,79] and cyclin D1 is frequently elevated in breast and prostate cancers [80,81]. Interestingly, the D1a isoform of cyclin D1 acts as an androgen-induced transcriptional repressor of AR via direct binding to the AR amino-terminus [82].…”
Section: Integrated Sr Actions In Gene Expressionmentioning
confidence: 99%